We Care, We Share: Pelatihan Bahasa Inggris Dasar bagi Anak Didik Panti Asuhan - Fatimah Mulya Sari; Ingatan Gulo (Indonesian Journal of Community Services in Engineering & Education (IJOCSEE), 2023)
The community service activity aims to build the trainees' self-confidence in the use of basic English in everyday life and enhance the participants' learning enthusiasm during the English training. This service activity has been carried out at the Kasih Nusantara Orphanage for 4 (four) months. The number of training participants consisted of 30 people with educational backgrounds starting from elementary school, junior high school, and high school. In the implementation process, the English training provided is in the form of lectures, questions and answers, discussions, and simulations/practices. The results achieved are that the trainees have increased their ability and confidence in using English. In addition, the response given was positive to the materials provided by the teaching team. Therefore, this community service activity might foster a sense of concern for partners in the application of their knowledge and knowledge so that they have a positive impact on the target partners of this activity.